Analysis Of The Influence Of Content Personalisation On Consumer Purchasing Decisions In The E-Commerce Industry - Hakim, Muhammad Arif Abdul (Marcha Institute, 2023)
This research investigates the influence of content personalisation on consumer purchase decisions in the e-commerce industry, with an emphasis on the application of Consumer Education and Awareness methods. Through a case study on FashionTrend, an e-commerce platform, the results show that the Consumer Education and Awareness approach is effective in improving users' understanding of content personalisation practices and the importance of data privacy. The results show an increase in consumer trust, customer satisfaction, and regulatory compliance. However, this study has limitations in the scope of the solution methods used. Therefore, future research is recommended to delve deeper into the implications of Consumer Education and Awareness strategies comparatively with other approaches, as well as explore the contextual factors that influence their effectiveness.